A two-dimensional cof-based separation membrane, a preparation method and a metal ion separation method

CN120459825BActive Publication Date: 2026-11-03NANJING TECH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510317938.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-12-10
Filing Date
2025-03-18
Publication Date
2026-11-03
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

Traditional membrane materials struggle to simultaneously meet the requirements of high throughput and high selectivity in the field of ion separation, especially for monovalent metal ions, where the separation effect is poor. Furthermore, conventional COF preparation methods result in low two-dimensional order and difficulty in stripping.

Method used

A COF separation membrane was prepared by combining two-dimensional COF nanosheets with reduced graphene oxide and polyanionic materials using interfacial polymerization technology and a three-phase interfacial method. By controlling the interlayer potential and crystal form of the COF nanosheets, a low negative charge separation layer was formed, which enhanced the mass transfer and separation ability of monovalent metal ions.

Benefits of technology

It achieves efficient and selective retention and transfer of monovalent metal ions. The separation membrane has good stability and anti-interference ability. The process is simple and low-cost, and it is suitable for the separation of monovalent metal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120459825B_ABST
    Figure CN120459825B_ABST
Patent Text Reader

Abstract

The application discloses a two-dimensional COF-based separation membrane, a preparation method and a metal ion separation method. The COF sheet used in the method has a good layered structure and a good crystal form. After being mixed with graphene oxide (rGO) and a polyanion material, the interlayer spacing and the surface potential of the COF are changed, and then the separation membrane is obtained through an interfacial polymerization method. The preparation method is simple in process, convenient in operation, mild in conditions, low in cost and easy to implement, and the prepared membrane has a good mass transfer rate and selectivity for monovalent metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-dimensional COF, specifically relating to a method for preparing and applying the interlayer potential of anionic COF. Background Technology

[0002] In today's world, the rational use of resources and environmental protection have become two major challenges facing the globe. Especially in water resource management, efficient and precise water treatment technologies are crucial for alleviating the water crisis and preventing water pollution. Membrane separation technology, as an energy-saving and environmentally friendly separation method, is widely used in many fields such as seawater desalination, wastewater treatment, and pure water production. However, faced with complex and varied separation tasks, traditional membrane materials often struggle to simultaneously meet the requirements of high throughput and high selectivity. Particularly in the field of ion separation, achieving highly selective retention and efficient transfer of specific ions remains a pressing challenge.

[0003] In recent years, two-dimensional covalent organic frameworks (2D COFs), as an emerging class of porous materials, have shown unprecedented potential in separation science due to their unique two-dimensional sheet-like structure, well-organized nanopores, abundant chemical functional groups, and excellent stability. Unlike three-dimensional COFs, 2D COFs possess a more open pore system, which facilitates rapid diffusion of substances; at the same time, their planar structure endows the materials with higher crystallinity and mechanical strength, making them more suitable for preparing high-performance separation membranes.

[0004] Interfacial polymerization, as a mature membrane preparation strategy, can construct dense and continuous separation layers by initiating in-situ polymerization reactions at the interface between two phases, and has been successfully applied to the synthesis of various polymer membranes. The ingenious integration of interfacial polymerization with 2D COF materials can not only fully leverage the unique advantages of 2D COFs, but also effectively address their limitations in practical applications, such as insufficient mechanical strength.

[0005] On the other hand, during the lithium extraction process from salt lakes, the potassium in the brine... + The presence of Li + The purity of the separated material is affected, and conventional sun-drying methods suffer from insufficient removal, while adsorption methods have problems with low separation efficiency and high adsorbent consumption. Furthermore, nanofiltration methods also have issues with the nanofiltration membrane's ability to remove K+. + and Li + The problem lies in the low separation coefficient. In particular, the surface electronegativity of nanofiltration membranes makes the membrane surface susceptible to Li... + and K + The electric charge effect causes both to pass through simultaneously, thus affecting separation.

[0006] In addition, conventional preparation methods for COF materials include solvothermal synthesis, microwave heating synthesis, and ionothermal synthesis. These methods usually suffer from problems such as poor two-dimensional order of the prepared COF particles and difficulty in exfoliation. Solvothermal synthesis mainly produces powders, see Coordination Chemistry Reviews 514(2024)215873. Summary of the Invention

[0007] One of the technical problems solved by this invention is that the presence of negative charge on the surface of COF membranes leads to low separation efficiency of mixed metal ion solutions. This invention provides a method for preparing anion-modified COF interlayer potential and its application. The COF separation membrane obtained by this method has less negative charge and can have good mass transfer and separation capabilities for monovalent metal ions, resulting in a good separation effect for monovalent metal ions.

[0008] A two-dimensional COF-based separation membrane includes a base membrane and a selective separation layer on the surface of the base membrane. The selective separation layer mainly contains polymers, including two-dimensional COF nanosheet materials, and also contains reduced graphene oxide (rGO) and / or polyanionic materials. The two-dimensional COF nanosheets are anionic, and the separation membrane has a zeta potential value lower than that of the two-dimensional COF nanosheets.

[0009] The two-dimensional COF nanosheets have a zeta potential of -80mV to -20mV; the zeta potential of the separation membrane is -40mV to -5mV.

[0010] The COF nanosheet material is selected from one of the following: boric acid, triazine, imine, phenylhydrazone, polyimide, phthalocyanine, or porphyrin.

[0011] The loading of two-dimensional COF nanosheets on the surface of the separation membrane is 5-20 mg / cm³. 2 .

[0012] The imine-based COF nanosheets have the following structure:

[0013]

[0014] The polymer is polyamide; the polyanionic material refers to one or more of polystyrene sulfonate, polyacrylate, polyvinyl alcohol sulfonate, and polyacrylonitrile salt; the base film is made of one or more of polyethersulfone, polypropylene, polyester, polyamide, polyurethane, polyvinylidene fluoride, and polyimide.

[0015] The above-mentioned method for preparing the two-dimensional COF-based separation membrane includes the following steps:

[0016] Step 1: Prepare an aqueous solution containing two-dimensional COF nanosheets, aqueous monomers, and reduced graphene oxide (rGO) and / or polyanionic materials;

[0017] Step 2: After applying the aqueous solution to the surface of the base membrane, the oil phase solution containing the oil phase monomer is then brought into contact with the base membrane to undergo an interfacial polymerization reaction, thus obtaining the separation membrane.

[0018] The aqueous phase monomer is one of amine monomers or piperazine monomers, and the oil phase monomer is an acyl chloride monomer.

[0019] In the aqueous solution, the weight ratio of two-dimensional COF nanosheets, aqueous monomers, reduced graphene oxide, and polyanionic materials is (4-20):(2-10):(0.00-0.08):(0.05-0.15).

[0020] In step 2, the aqueous solution is applied by one of the following methods: filtration, soaking, or scraping. The aqueous solution has undergone ultrasonic dispersion treatment. The contact time between the oil phase monomer and the base film is 5-10 minutes, and the contact method is soaking.

[0021] A method for separating metal ions involves contacting a solution containing metal ions with a two-dimensional COF-based separation membrane, allowing the metal ions to be retained or permeate; the solution containing metal ions may or may not be pressurized.

[0022] The solution containing metal ions contains K. + and Li + , making K + Compared to Li + More permeates through the membrane.

[0023] The second technical problem solved by this invention is the low two-dimensional order and difficulty in exfoliation of COF two-dimensional nanosheets obtained by traditional solvothermal methods. This invention provides a controllable method for preparing COF two-dimensional nanosheets based on a three-phase interface method. The COF sheets obtained by this method have a good layered structure and exhibit good crystallinity as characterized by XRD.

[0024] A method for preparing COF two-dimensional nanosheets includes the following steps:

[0025] In the reaction vessel, the lower oil phase solution and the aqueous phase solution are added sequentially, so that the aqueous phase solution is on top, and then the upper oil phase solution is slowly added and the reaction is carried out to obtain a reaction solution containing COF material.

[0026] The upper oil phase solution and the lower oil phase solution contain a first monomer and a second monomer that can form covalent bonds to obtain COF materials, respectively.

[0027] The COF material is selected from one of the following: boric acid, triazine, imine, phenylhydrazone, polyimide, phthalocyanine, or porphyrin.

[0028] The COF material is an imine material, and the first monomer and the second monomer are an amine-containing monomer and an aldehyde-containing monomer, respectively; the aqueous solution is an acidic aqueous solution.

[0029] The concentration of the first monomer in the upper oil phase solution is 1-20×10⁻⁶. -3 The concentration of the second monomer in the lower oil phase solution is 0.5-15 × 10 mmol / mL. -3 mmol / mL; the acid concentration in the aqueous phase solution is 1-6 M.

[0030] The volume ratio of the upper oil phase solution, the aqueous phase solution, and the lower oil phase solution is 30-60:10-30:50-100.

[0031] The volume of the upper oil phase solution added per minute is 1-5% of the total volume of the lower oil phase.

[0032] The reaction time is 5-50 hours, and the reaction temperature is 1-50℃.

[0033] The application of COF two-dimensional nanosheets obtained by the above method in the preparation of metal ion separation membranes.

[0034] Beneficial effects

[0035] 1. The COF of this invention is a two-dimensional porous material with a large number of crystal lattices on its surface, exhibiting excellent mass transfer and separation capabilities for monovalent metal ions. 2. The preparation method of the separation membrane of this invention is simple, convenient, mild, low-cost, and easy to implement. The resulting separation membrane exhibits strong selective adsorption, strong anti-interference ability, good stability, fast adsorption rate, and easy separation, making it suitable for monovalent metal ions. Attached Figure Description

[0036] Figure 1 The infrared spectra of rGO-TPPA-PSSNA and the control sample prepared in Example 1 of this invention are shown.

[0037] Figure 2 This is a TEM image of the COF obtained in Example 1 of the present invention.

[0038] Figure 3 SEM images of rGO-TPPA-PSSNA and a control sample prepared in Example 1 of this invention.

[0039] Figure 4 Potentiograms of rGO-TPPA-PSSNA and a control sample prepared in Example 1 of the invention.

[0040] Figure 5 The images show the separation diagrams of monovalent metal ions for rGO-TPPA-PSSNA and the control sample prepared in Example 1 of this invention.

[0041] Figure 6 TEM image of COF obtained in Experiment 2 for comparison.

[0042] Figure 7 The image shows the XRD patterns of COF and rGO obtained in Example 1 of this invention. Detailed Implementation

[0043] Example 1

[0044] 1. The preparation method of rGO-TPPA-PSSNA (TPPA is short for COF) is as follows:

[0045] (1) COF nanosheets were prepared by a three-phase interface method. In the preparation process, the lower layer solution and the acetic acid aqueous solution were poured into a 150 mL high collar beaker in sequence. The upper layer solution was drawn into a 50 mL disposable syringe and placed vertically on the beaker. A micro-injection pump was used to add the solution dropwise at a rate of 0.2 mm / min to 1.1 mm / min. More specifically, the upper oil phase was 2,5-diaminobenzenesulfonic acid (0.15 mmol) dissolved in N,N-dimethylformamide (50 mL), and the lower oil phase was 1,3,5-trimethylaldehyde pyrogallol (0.1 mmol) dissolved in dichloromethane (80 mL). 20 mL of 3M acetic acid aqueous solution was added to the intermediate aqueous phase. When adding the upper amine-containing solution, the solution was slowly added using a microfluidic control method (1.1 mm / min). The total addition time was about 70 min. After 3 days, negatively charged COF nanosheets were obtained.

[0046] (2) The COF nanosheets (0.8 mg / mL, 10 mL) prepared in (1) were mixed with rGO (1 mg / mL, 4 mL) and PSSNA (polystyrene sulfonate, 1 wt% 5 mL), diluted to 200 mL, and 2 wt% 5 mL p-phenylenediamine solution was added. The mixture was sonicated for 30 min and then the rGO-TPPA-PSSNA membrane was prepared by vacuum filtration. The base membrane used was a polyacrylonitrile ultrafiltration membrane with a MWCO of 1 million and a diameter of about 3.5 cm. The prepared membrane was cured by immersing it in a hexane solution of triacryl chloride (0.2 wt%) for 10 min and then dried in an oven at 60 °C for 10 min.

[0047] Comparative Experiment 1

[0048] Five blank control groups were included, which differed from Example 1 in that PAANA and TPPA were not added in blank control group 1, TPPA was not added in blank control group 2, PAANA and rGO were not added in blank control group 3, rGO was not added in blank control group 4, and PAANA was not added in blank control group 5.

[0049] Comparative Experiment 2

[0050] Compared to the COF nanosheet preparation process in Example 1, the dropping rate of the upper oil phase solution was not controlled. The characterization results of the obtained COF nanosheets are as follows: Figure 6 Transmission electron microscopy (TEM) images show that the morphology of TPPA nanosheets underwent a significant transformation after microfluidic modification, with their average size expanding to approximately 8.5 μm in length and 3.5 μm in width. This represents a marked improvement in morphology compared to the uncontrolled material, which was 1.7 μm long and 4.2 μm wide. Simultaneously, the crystal lattice structure became denser, and the overall regularity was significantly enhanced, confirming the positive effect of microfluidic technology on the quality of COF nanosheets when controlling the third-phase flow rate.

[0051] The rGO-TPPA-PSSNA prepared in Example 1 of this invention and the blank control group were characterized and analyzed.

[0052] 1. The results of Fourier transform infrared spectroscopy are as follows: Figure 1 As shown.

[0053] Figure 1 The infrared spectra of rGO-TPPA-PSSNA prepared in Example 1 of this invention and the control group are shown.

[0054] The infrared spectra show that the peaks and peak shapes of the rGO-TPPA-PSSNA and the control group are basically the same. The rGO membrane contains -OH groups, while the others do not. The membrane containing TPPA has peaks in the 800-1400 cm⁻¹ range. -1 It has the characteristic peak of -SO3H.

[0055] 2. Transmission electron microscopy (TEM) analysis showed that the COF is a layered structure with a well-defined lattice. The test results are as follows: Figure 2 As shown.

[0056] 3. Figure 3 The images show SEM images of rGO-TPPA-PSSNA prepared in Example 1 of this invention and the control group.

[0057] As can be seen from the SEM image, the surface distribution of rGO-TPPA-PSSNA prepared by Example 1 of the present invention is relatively uniform.

[0058] 4. Figure 4The images show the potential diagrams of rGO-TPPA-PSSNA prepared in Example 1 of this invention and the control group.

[0059] As can be seen from the potential diagram, the potential of the rGO-TPPA-PSSNA prepared in Example 1 of the present invention increases with the addition of PSSNA; by comparing the TPPA film with the rGO-TPPA film, it can also be seen that the addition of rGO also helps to improve its potential, and the synergy between PSSNA and rGO can more effectively reduce its negative charge.

[0060] 5. The specific application is as follows: The rGO-TPPA-PSSNA membrane is placed in a U-shaped cell with deionized water and a mixed solution of 0.1 mol KCl and LiCl on the two sides respectively, and allowed to diffuse freely at 25℃ for 24 h. Figure 5 The diagram shows the separation performance of rGO-TPPA-PSSNA prepared in Example 1 of this invention and the control group.

[0061] 6. Transmission electron microscopy (TEM) analysis revealed that the uncontrolled velocity COF (CoF-formed Fiber) layers lacked a well-defined lattice structure. The test results are as follows: Figure 6 As shown.

[0062] As can be seen from the separation performance, the performance of rGO-TPPA-PSSNA prepared in Example 1 of this invention increases with the addition of PSSNA, and can be improved by 40% compared with TPPA membrane.

Claims

1. A method for separating metal ions, characterized in that, The process involves contacting a solution containing metal ions with a two-dimensional COF-based separation membrane, allowing the metal ions to be retained or permeate; the solution containing metal ions contains K. + and Li + , making K + Compared to Li + More permeable membrane layers; solutions containing metal ions may be pressurized or unpressurized; The two-dimensional COF-based separation membrane includes a base membrane and a selective separation layer on the surface of the base membrane. The selective separation layer contains a polymer, including two-dimensional COF nanosheets, and also contains reduced graphene oxide and polyanionic materials; the two-dimensional COF nanosheets are anionic. The two-dimensional COF nanosheets have a zeta potential of -80mV to -20mV; the zeta potential of the separation membrane is -40mV to -5mV; the two-dimensional COF nanosheets are imine-based COF nanosheets. The imine-based COF nanosheets have the following structure: ; The preparation method of the two-dimensional COF-based separation membrane includes the following steps: Step 1: Prepare an aqueous solution containing two-dimensional COF nanosheets, aqueous monomers, reduced graphene oxide, and polyanionic materials; Step 2: After applying the aqueous solution to the surface of the base membrane, the oil solution containing the oil monomer is then brought into contact with the base membrane to undergo an interfacial polymerization reaction, thus obtaining the separation membrane.

2. The separation method according to claim 1, characterized in that, The aqueous phase monomer is an amine monomer, and the oil phase monomer is an acyl chloride monomer.

3. The separation method according to claim 1, characterized in that, In the aqueous solution, the weight ratio of two-dimensional COF nanosheets, aqueous monomers, reduced graphene oxide, and polyanionic materials is (4-20):(2-10):(0.00-0.08):(0.05-0.15).

4. The separation method according to claim 1, characterized in that, The loading of two-dimensional COF nanosheets on the surface of the separation membrane is 5-20 mg / cm³. 2 .

5. The separation method according to claim 1, characterized in that, The polymer is polyamide; the polyanionic material refers to one or more of polystyrene sulfonate, polyacrylate, polyvinyl alcohol sulfonate, and polyacrylonitrile; the base film is made of one or more of polyethersulfone, polypropylene, polyester, polyamide, polyurethane, polyvinylidene fluoride, and polyimide.

6. The separation method according to claim 1, characterized in that, In step 2, the aqueous solution is applied by one of the following methods: filtration, soaking, or scraping. The aqueous solution has undergone ultrasonic dispersion treatment. The contact time between the oil phase monomer and the base film is 5-10 minutes, and the contact method is soaking.

Citation Information

Patent Citations

  • Modified graphene film applied to monovalent and polyvalent metal ion separation and preparation method thereof

    CN107261857A

  • Nanofiltration membrane and preparation method thereof

    CN117358066A